(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study has motivated to identify Education teaching competency of college teachers working at various degree colleges in Tripura. Review of related literature has helped to frame the hypothesis; descriptive method and stratified random sampling technique was applied for the study. A standardized tool (Content Validity Index: 0.73 & Reliability level of .875) consisting 30 items was administrated to measure Education teaching competency from the selected sample of the study. Inferential statistics had been applied to draw inference from the hypothesis. The result indicates that the Chi-squire value 0.252 is not significant at 0.05 level of significance which means there is no significant association between ‘Age’ and ‘Education teaching competency’ of degree level teachers; Chi-squire value .642 is not significant at 0.05 level of significance which means there is no significant association of ‘Gender’ and ‘Education teaching competency’. Hence, it may be argued that individual attention must be given to poor performing students in Education subject; Education teachers belonging to degree colleges should give individual attention to each of the learners etc. Although, it has been acknowledged that there remains some limitations of the study, but from the findings and recommendations of the study, future road-map for further research can be sketched.